Powerful arguments: standards of validity in late imperial China - Hofmann, Martin; Kurtz, Joachim; Levine, Ari Daniel (Brill, 2020)
"The essays in Powerful Arguments reconstruct the standards of validity underlying argumentative practices in a wide array of late imperial Chinese discourses, from the Song through the Qing dynasties. The fourteen case studies analyze concrete arguments defended or contested in areas ranging from historiography, philosophy, law, and religion to natural studies, literature, and the civil examination system. By examining uses of evidence, habits of inference, and the criteria by which some arguments were judged to be more persuasive than others, the contributions recreate distinct cultures of reasoning. Together, they lay the foundations for a history of argumentative practice in one of the richest scholarly traditions outside of Europe and add a chapter to the as yet elusive global history of rationality"--
Includes index
Keywords: China; Aufsatzsammlung; Geschichte; Argumentation